Análisis de la aplicación de zirconio monolítico en estética dental - Vallejo Panchez, Karla Geovanna (2022)
ABSTRACT: The aim of this research work is to analyze “THE APPLICATION OF MONOLITHIC ZIRCONIA FRAMEWORKS” in dental esthetics, determining the use of this ceramic in these areas, by means of a review of scientific articles found in the last 5 years in various scientific databases such as Pubmed, Wiley, Elsevier, Scielo, Google Scholar. For the search and scientific review of the publications, the PICOS analysis methodology was used; in addition to the selection by inclusion criteria referring to rehabilitation with monolithic zirconia in the anterior areas, articles mentioning the process of elaboration and cementation of monolithic zirconia, the quality of the studies was validated by the average citation and the location of the journal in the Scimago ranking; obtaining a total of 70 articles. The results of the publications indicate that the monolithic zirconium has a great goodness to be used in esthetic areas, this area has excellent characteristics and advantages, providing in its elaboration a very accurate process, taking up less space unlike other ceramics inlays and the most important thing is that it has a high tooth resistance and a natural-looking appearance of tooth, the excellent aesthetics of zirconium compared with other ceramics is unquestionable on metal- ceramics, gives a superior fit than feldspathic porcelain reducing the risk of chipping. In addition, it does not present biological problems also it has been demonstrated with common criteria that this ceramic inlays must have a good biocompatibility.